Analisis Etika Guru Pendidikan Agama Kristen Berdasarkan Yakobus 3:1 Terkait Tanggung Jawab Pengajaran - Yusniar Dakhi; Viktorius Sagulu; Martinus Laia; Silfani Gili Lay (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study analyzes the ethics of Christian Religious Education teachers based on James 3:1, which emphasizes the great responsibility carried by those who teach in the context of educational ministry. The research aims to examine the relevance of biblical principles regarding the role and duties of teachers with the implementation of the professional code of ethics for Christian Religious Education teachers in Indonesia. Teachers are not only responsible for delivering academic knowledge but also serve as moral and spiritual role models whose words, attitudes, and actions significantly influence students’ faith development. This study uses a descriptive qualitative method through literature analysis, including the interpretation of James 3:1, ethical guidelines, and theological-pedagogical studies. The findings show that James 3:1 provides a strong warning for teachers to be cautious, responsible, and accountable in their teaching practices, as their judgment before God is greater. In conclusion, the ethics of Christian Religious Education teachers reflect their faith commitment in carrying out their responsibilities with integrity.